Effect of milk vs. sugar-sweetened beverage supplementation on bone development in pre-pubertal pigs as model for children. Issue 1 (14th December 2020) - Batty, Brandon; Kutzler, Michelle; Campbell, Scott; Turner, Russell; Bionaz, Massimo
Abstract: Milk consumption has long been associated with better bone development in children, contrary to sugar-sweetened beverages (SSB); however, stronger evidence are needed. Therefore, this study aimed to use a pig model for growing children to evaluate the effect of milk vs. SBB consumption on the developing skeleton. For this, we used 24 pre-pubertal pigs (12 in Experiment 1, 8 males and 4 females, and 12 in Experiment 2, all males) randomly split into two groups to receive up to 750 mL of whole milk supplementation or an isocaloric maltodextrin solution (as SSB) for 13 or 11 weeks. Ultrasonography was used throughout the trial to record in vivo bone growth. The pigs were euthanised, and bones of the appendicular skeleton and the mandible were collected and measured with Dual X-Ray Absorptiometry (DEXA). A three-point bending test was used for biomechanical testing. After fracture, the cortical bone thickness was measured at three regions of the femur. Of the DEXA measurements taken, only the bone mineral density of the mandible was lower in pigs receiving milk vs. SSB. Compared to SSB, pigs consuming milk had also a larger occlusal surface thickness indicating lower teeth grinding, suggesting a calming effect of the milk. There was no difference in any biomechanical tests. In femur, the medial cortical was thicker in the SSB group, while the lateral cortical was thicker in the group receiving milk. Overall, there appears to be no effect of short-term milk supplementation on bone growth, mineral density and strength. Highlights: Larger bone density and size was observed in male vs. female before puberty. Three cups of whole milk per day for 3 months did not improve bone density and strength compared to isoenergetic sugar-sweetened beverage in prepubertal pigs used as model for growing children despite higher amount of calcium in the diet. Lower bone density in the ramus of the mandible and less teeth grinding indicated a reduced stress in the animals feed with milk.